Analisis Gaya Bahasa Pada Lirik Lagu Dalam Album The Second Step: Chapter Two Karya Treasure - Entik Mayyiratu; Rahmi Oktayory Wikarya (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2025)
Language style is the use of a specific variety to achieve certain effects. Language style adds a sense of beauty to a literary work. The use of language style in music lyrics needs to be studied to avoid misinterpretation of the song’s meaning, as language style contains implied meanings that require a deep understanding to grasp the full meaning of the song. This research targets to describe how the lyrics use language style songs from the album The Second Step: Chapter Two by Treasure, using Sutedi’s theory of language style. The descriptive method is mixed with a qualitative studies approach in this observe. music lyrics with specific language styles make up the general public of the information used in this study. The data sources are 7 song titles from the album The Second Step: Chapter Two by Treasure. The findings of the observe lead us to the belief that there are 24 music lyrics that employ language patterns. 17 data using metaphorical language styles with details: 8 conceptual metaphor data, 4 orientational metaphor data, 2 ontological metaphor data, and 3 channel metaphor data. Next, 5 data that use metonymy language style with details: 1 metonymy data that relates to the place of something and its contents (youki-nakami), and 4 metonymic data related to cause and effect (gen-in—kekka).Then there are 2 data that use synecdoche language style.